La legge n. 180/1978 quale fattore di revisione dei paradigmi. Dall’immunitas alla communitas (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The law that in 1978 reformed the psychiatric assistance in Italy represented an historical passage not only respect to the policy of the assistance to mentally ill people but also for the cultural and social approach to psychiatric illness. The abolition of mental hospital, the return of the citizenship rights and the beginning of the process of destigmatization of mental illness are a sign of scientific, anthropological and legal paradigms shift. Forty years after the law, despite contradictions, gaps and the chronic underfunding of psychiatric services, the “Basaglia” law has led to a great phenomenon of liberation, an extraordinary journey that is still unfinished.
Keywords: Psychiatry; rights; psychiatric reform; paradigm